2015
DOI: 10.1002/jsfa.7325
|View full text |Cite
|
Sign up to set email alerts
|

Espresso coffee residues as a nitrogen amendment for small-scale vegetable production

Abstract: The study showed an inhibition of N and P mineralisation and a reduction of plant germination and growth. Further research is required to determine whether this is related to the immobilising capacity of the residue or possibly due to the presence of caffeine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It is thought that polyphenolic components such as chlorogenic acid (CGA) are phytotoxic through mechanisms including interference with plant metabolic pathways, membrane cell oxidation and immobilisation of soil N and P [34]. Caffeine may also present allelopathic activity through prevention of N mineralization [35]. Yet, SCG polyphenols are thought to enhance mineral uptake of crops through their binding capacity [36,37].…”
Section: Petri-dish Toxicology Testsmentioning
confidence: 99%
“…It is thought that polyphenolic components such as chlorogenic acid (CGA) are phytotoxic through mechanisms including interference with plant metabolic pathways, membrane cell oxidation and immobilisation of soil N and P [34]. Caffeine may also present allelopathic activity through prevention of N mineralization [35]. Yet, SCG polyphenols are thought to enhance mineral uptake of crops through their binding capacity [36,37].…”
Section: Petri-dish Toxicology Testsmentioning
confidence: 99%
“…Caffeine is an alkaloid that has a toxic effect on a broad range of organisms at variable concentrations. Caffeine reduces N availability to plants and inhibits germination and plant growth [64]. Addition of SCG to soil has been found to reduce the growth of several crop species [53,64].…”
Section: Relationships Among Lettuce Growth Disease Incidence/severit...mentioning
confidence: 99%
“…Caffeine reduces N availability to plants and inhibits germination and plant growth [64]. Addition of SCG to soil has been found to reduce the growth of several crop species [53,64]. In order to avoid these drawbacks, SCG must be composted before their use in agriculture.…”
Section: Relationships Among Lettuce Growth Disease Incidence/severit...mentioning
confidence: 99%
“…Regarding the utilization of coffee by-products, current research mainly focuses on biochar production and composting coffee grounds. It has been shown that replacing chemical fertilizers with coffee grounds can increase soil respiration rate, soil organic carbon, total nitrogen, and trace element content [18][19][20], promote nutrient absorption by crops, and boost crop photosynthetic efficiency and yield [21]. Coffee husks, including pectin, are rich in organic and mineral nutrients.…”
Section: Introductionmentioning
confidence: 99%